Clima e produção do espaço urbano: contribuição ao estudo da Geografia do Clima no contexto das cidades de São Carlos e Marília - Rampazzo, Camila Riboli [UNESP] (2015)
On the studies about urban environmental problems, mainly the ones related to climate and temperature data, it is desired to develop the benchmark of triggers that initiate environmental issues. In this context, the dissertation entitled Climate and Production of Urban Space: Contribution to the Study of Climate Geography in the Context of the Cities São Carlos and Marilia aims to analyze and identify the occurrence and spatiotemporal distribution of thermohygrometric differences and similarities between Marília/SP and São Carlos/SP and their distinct interurban spaces. To this end, different urban shapes and structures resulting of the their production are considered. From the analytic perspective of Climate Geography, we sought to contribute to the discussions about the complex associations between climate and urban space, considering that different degrees of urban susceptibility are applicable to different degrees of technification employed in the different spaces. In order to do so, the historic context of the alterations in the cities' urban spaces was discussed and afterwards, geographic sectors were throughly described by means of geoenvironmental indicators, of urban morphology and physiographics. Next, we sought to identify the places of occurrence and magnitude of the gradients of temperature and relative humidity by means of fixed and mobile thermohygrometric records. It was found not only the existence of urban climate in São Carlos and Marilia, with magnitudes above 10ºC and 6ºC...